2007
DOI: 10.1186/1471-2334-7-82
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of parents and professionals to neonatal BCG vaccination in light of recent UK policy changes: A questionnaire study

Abstract: Background: Universal BCG vaccination in the UK ended in 2005. The new vaccination policy instead offers a number of different forms of selective vaccination to newborns based on risk of acquiring TB. We set out to assess the attitudes and knowledge of both parents and professionals to the new policy for neonatal BCG vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Even if regular changes are required to follow the evolution of advanced vaccinology and epidemiological characteristics, their impact on the health professional’s practices should be taken into account. In Great Britain, two years after the cessation of routine BCG vaccination in 2005 and the implementation of targeted vaccination, two-thirds of parents and professionals interviewed were not aware of the new recommendation [25]. About multiplying specific indications, a French study of 2009 on the determinants of BCG vaccination showed that the probability of an eligible child being properly vaccinated increased with the number of instructions known by the physician [26].…”
Section: Discussionmentioning
confidence: 99%
“…Even if regular changes are required to follow the evolution of advanced vaccinology and epidemiological characteristics, their impact on the health professional’s practices should be taken into account. In Great Britain, two years after the cessation of routine BCG vaccination in 2005 and the implementation of targeted vaccination, two-thirds of parents and professionals interviewed were not aware of the new recommendation [25]. About multiplying specific indications, a French study of 2009 on the determinants of BCG vaccination showed that the probability of an eligible child being properly vaccinated increased with the number of instructions known by the physician [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings suggest that some health professionals involved in the BCG vaccination programme might be unfamiliar with recommended eligibility criteria; this could contribute to low coverage rates. 21 A standardised pathway to identify eligible infants, with clear responsibilities and roles and regular training of staffs involved, could contribute to high vaccination coverage in PCTs with selective vaccination policy. 22 23 In addition to the correct identification of infants at risk, assuring that the vaccine is administered is another challenge of a targeted vaccination policy.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, routine BCG vaccination ceased in 1985, and vaccination of children now effectively relies on the initiative of parents. A study in the United Kingdom reported that only 6% of parents were aware of national BCG vaccination recommendations 3 . We aimed to determine the proportion of mothers from high‐TB‐prevalence countries giving birth in Australia who were planning to travel to these countries with their newborn child, and to assess their knowledge of the need to BCG‐vaccinate their child.…”
mentioning
confidence: 99%